BUDAYA KESELAMATAN PASIEN DI RUANG RAWAT INAP RUMAH SAKIT X KABUPATEN JEMBER - Yennike Tri Herawati (Jurnal Ilmu Kesehatan Masyarakat, 2015)
Patient safety is a priority for implementation of the five important safety issues in hospital, because of patient safety issues related to the quality and image of the hospital it self. Diversity and regularity of the service if it is not managed properly can occur Safety Patient Incident, it’s consisting of Adverse Event, Near Miss, Incidentand Hazard (Depkes,2006). Based on data report of patient safety incidents X Hospital at JemberDistric 2011 to 2012 anincrease of patient safety incidents. It is appropiate with national guidelines hospitalpatient safety, the first step patient safety program at the hospital is building a patient safetyculture. The purpose of this research is a deskriptif study was to describe patient safety culture at inpatient of Hospital X Jember District. Indepth interview do to inpatient nurses using interview guide. Nurses who responded to as many 113 nurses wereselected by proportional random sampling.This study using cross sectional approach. The results showed that the indicator of patient safety culture for cooperation in both categories, communication in both categories, leadership in fairly categories, reporting in fairly categories and response is not punishing also in fairly categories. The conclusion of this study is the need for improvements to the leadership indicators, reporting, and response is not to punish.Key words : Patient, culture, nurse